Cooperação Sul-Sul, Investimentos Externos e Desenvolvimento: Existem novas perspectivas a partir do sul global? - Marta Zorzal e Silva (Cadernos de Estudos Africanos)
The text describes the relations and tensions that characterize the theme of development, external cooperation and foreign investments directed towards the so-called emergent economies of the South-South axis. It does so in order to reflect upon some aspects of this process. Among these are: a) the separate strands of thinking that contest the legitimacy of the meaning of the word development in the area of academic, political and societal debate; b) the power shaped by technical and productive networks and institutions when this process is set in motion; c) the international cooperation across the South-South axis, started by the BRICS constitution; and d) the aspects relative to the different rationales whose path cross within the sphere of these relations. The case of Mozambique is cited as an empiric reference so as to problematize the rationales and ideologies modeled on the different forms of development that “travel” from industrialized to non-industrialized countries. We conclude by showing certain trends seen in the direct investments done by the multinational corporation Vale S.A. in the Tete Province, in Mozambique, which aims at showing how different conceptions and visions of processes of development intertwine and conflict, in a context in which global dominance takes over local dominance.